2022
DOI: 10.1099/mgen.0.000813
|View full text |Cite
|
Sign up to set email alerts
|

Core-, pan- and accessory genome analyses of Clostridium neonatale: insights into genetic diversity

Abstract: Clostridium neonatale is a potential opportunistic pathogen recovered from faecal samples in cases of necrotizing enterocolitis (NEC), a gastrointestinal disease affecting preterm neonates. Although the C. neonatale species description and name validation were published in 2018, comparative genomics are lacking. In the present study, we provide the closed genome assembly of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…In this study, strains with core genes at 95% and 99% thresholds in the highly diverse S. aureus population finally entered the plateau phase, indicating that there are indeed a certain number of essential genes in this species. However, the number of core genes was not as high as previously thought ( 11 13 ). In the case of extreme strain diversity, we obtained a theoretical value that is relatively low in the number of core genes generally recognized in the literature.…”
Section: Discussioncontrasting
confidence: 70%
“…In this study, strains with core genes at 95% and 99% thresholds in the highly diverse S. aureus population finally entered the plateau phase, indicating that there are indeed a certain number of essential genes in this species. However, the number of core genes was not as high as previously thought ( 11 13 ). In the case of extreme strain diversity, we obtained a theoretical value that is relatively low in the number of core genes generally recognized in the literature.…”
Section: Discussioncontrasting
confidence: 70%
“…In contrast, the IM group showed enrichment in amino acid metabolism, xenobiotic biodegradation and metabolism, lipid metabolism, metabolism of other amino acids, terpenoids, and polyketides, and substance dependence. In the functional prediction analysis, it was found that the homologous genes of some prokaryotic microbiomes may be annotated to the metabolic pathway of eukaryotic organisms ( 39 41 ). In this case, we assume that the genes of these bacteria may be related to the two-component regulatory system, which will eventually reveal certain pathways that are not related to bacterial metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to clindamycin, tetracycline and β-lactams has been reported for Clostridium spp. 3 , 22 , 35–38 A retrospective study analysing the antimicrobial susceptibility of gas gangrene-forming Clostridium spp. over a 10 year period in Hungary reported resistance of up to 6.8% and 8.5% to penicillin and clindamycin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…De novo assembly of the 35 genomes was performed as previously described. 22 Comparison of each housekeeping gene sequence was performed using the NCBI multisequence advanced BLAST software. 23 An allele number is assigned to each unique sequence.…”
Section: Methodsmentioning
confidence: 99%